Tumor necrosis factor promotes doublecortin-like kinase 1 expression and cellular reprogramming in intestinal epithelial cells leading to neoplastic transformation - Huang, Lin; Li, Tianqi; Huang, Xu; Chen, Xiaoxi; Ju, Yuanyuan; Xu, Lili; Ma, Chunhua; Tao, Yumei; Yang, Yonghong; Bian, Xiaoyun; Huycke, Mark M.; Wang, Xingmin (Cell communication and signaling, 2025)
Background Tumor necrosis factor (TNF) is a critical mediator in chronic inflammation and colorectal cancer (CRC) progression. However, whether and how prolonged TNF exposure triggers CRC is not fully understood. Methods TNF-induced expression of Dclk1 , a cancer stem cell (CSC) marker, was assessed in IEC-6 intestinal epithelial cells, murine models, and colon organoids. TNF-induced reprogramming of intestinal epithelial cells was investigated through single-cell RNA sequencing and cellular transformation assayed by xenograft tumor model. Results We observed a significant increase in Dclk1 in the intestines of TNF -transgenic mice and TNF-treated IEC-6 cells. Notably, DCLK1 expression correlated positively with inflammation, TNF levels, and TNFRSF1a in human subjects. Silencing of Tnfrsf1a markedly reduced Dclk1 expression, underscoring the role of TNF-Tnfrsf1a axis in the regulation of Dclk1 expression. Furthermore, Dclk1-positive cells were significantly elevated in the intestines of TNF-treated wild-type mice, but not in Tnfrsf1a −/− mice, compared to controls. Inhibition of NFκB and c-Myc also led to a marked reduction in Dclk1 expression. Intriguingly, colonic organoids derived from TNF -transgenic mice exhibited increased numbers and sizes, whereas those from Tnfrsf1a −/− mice showed the opposite trend. Single-cell RNA sequencing revealed that prolonged TNF exposure induced CSC emergence through the reprogramming of Dclk1-positive tuft cells and activation of CRC-related pathways. Critically, prolonged TNF treatment resulted in neoplastic transformation of intestinal epithelial cells, leading to xenograft tumor formation in immunodeficient mice. Conclusions These findings provide novel insights into how chronic inflammation drives the genesis of intestinal CSCs and fosters CRC development, highlighting potential therapeutic targets for combating colitis-associated colorectal cancer.